2023
DOI: 10.3390/agronomy13041095
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Soil-Applied Humic Ameliorative Amendment on the Yield Potential of Switchgrass Panicum virgatum L. Cultivated under Central European Continental Climate Conditions

Abstract: The yield potential of switchgrass was verified by testing seven cultivars in a small-scale experiment carried out from 2018 to 2022 on Gleyic Fluvisol under Central European conditions. The treatments are as follows: pre-sowing (i/HA) soil humic preparation Humac AGRO (based on leonardite) with an ameliorative dose of 1000.0 kg ha−1 or (ii/NPK) basic nutrition with a dose of 220.0 kg ha−1 NPK; an annual dose of 70 kg ha−1 N was applied to both treatments (HA, NPK) and compared to (iii/UC) untreated control. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…claim that while industrial hemp was positively affected by nitrogen fertilisation up to 200 kg N/ha, the response to phosphorus and potassium fertilisation remained neglectable. However, the best option to evaluate lignocellulose quality is to provide the valuation in terms of quality content and quality yield as well, while an important impact on nutrition can be expected (Kron et al 2017;Tóth & Dupľák 2023). Pagnani et al (2018) also recorded the positive effect of plant growth-promoting rhizobacteria (PGPR) on the aboveground biomass of hemp, as well as the accumulation of plant secondary metabolites and consequently antioxidant capacity.…”
Section: Resultsmentioning
confidence: 99%
“…claim that while industrial hemp was positively affected by nitrogen fertilisation up to 200 kg N/ha, the response to phosphorus and potassium fertilisation remained neglectable. However, the best option to evaluate lignocellulose quality is to provide the valuation in terms of quality content and quality yield as well, while an important impact on nutrition can be expected (Kron et al 2017;Tóth & Dupľák 2023). Pagnani et al (2018) also recorded the positive effect of plant growth-promoting rhizobacteria (PGPR) on the aboveground biomass of hemp, as well as the accumulation of plant secondary metabolites and consequently antioxidant capacity.…”
Section: Resultsmentioning
confidence: 99%
“…The humus content in the soil, soil pH, and content of available P, K, Mg, B, Mn, Cu, Zn, and Fe were also increased. Other studies conducted by Tóth et al [58] showed a positive effect of Humac Agro, when used at a dose of 1 t ha −1 , on the yield and biometric parameters of switchgrass (Panicum virgatum L.). BCW has the ability to absorb and exchange ions between the soil solution and the solid phase.…”
Section: Interaction Of Brown Coal Waste and Mineral Fertilizationmentioning
confidence: 90%
“…For this purpose another 315 sets of biometric data were applied as independent variables. These complementary parameters (crop yield, plant height, and dry matter content at harvest) were the subject of the former paper ( [13]). Finally, the cultivar order based on the average DM yield achieved, as used in the tables, is listed in the results of the former paper.…”
Section: Methodsmentioning
confidence: 99%
“…The crop phytomass was collected and quality analyses were also performed in 2018-2022, despite the low switchgrass yield in the establishment year (2018). A more detailed description of the screening trial in terms of trial site, nutrition treatments, agronomy, weather and soil conditions, plant material, biometric parameters, and collection of plant samples is presented in a former paper [13].…”
Section: Pilot Screening Trials During 2018-2022mentioning
confidence: 99%